2018
DOI: 10.1016/j.ijnurstu.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

What makes it so difficult for nurses to coach patients in shared decision making? A process evaluation

Abstract: This study shows that changing practice nurses' role from medical experts to coaches in shared decision making is very complex and requires paying attention to skills and attitudes, as well as to contextual factors. Our results indicate that more time and training might be needed for this role transition. Moreover, it might be worthwhile to focus on organizational learning, in order to increase an organization's capacity to change work routines in a collaborative process. Future research into the development a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 49 publications
0
51
0
Order By: Relevance
“…Training in the skills and knowledge required for conversations about the decision-making process is needed. Other studies have already confirmed the successfulness of such training in decision coaching for nurses , coaching patients in decision-making for nurses (Lenzen, Daniels, van Bokhoven, van der Weijden, & Beurskens, 2018) and applying SDM about palliative chemotherapy for medical oncologists (Henselmans et al, 2019). Training may also increase awareness and clarity about nurses' supporting role in the decision-making process.…”
Section: Impactmentioning
confidence: 93%
“…Training in the skills and knowledge required for conversations about the decision-making process is needed. Other studies have already confirmed the successfulness of such training in decision coaching for nurses , coaching patients in decision-making for nurses (Lenzen, Daniels, van Bokhoven, van der Weijden, & Beurskens, 2018) and applying SDM about palliative chemotherapy for medical oncologists (Henselmans et al, 2019). Training may also increase awareness and clarity about nurses' supporting role in the decision-making process.…”
Section: Impactmentioning
confidence: 93%
“…Despite being so heavily embraced by scientific scholars and policymakers, formal implementation of SDM in practice has proven to be challenging . One key barrier seems to be the perceived time needed to practice SDM, addressing both risk communication and clarification of patients' values . Although clinicians generally support SDM, they are also often hesitant to practice it and often revert to a more authoritarian conversational model …”
Section: Introductionmentioning
confidence: 99%
“…3,[7][8][9][10] One key barrier seems to be the perceived time needed to practice SDM, [11][12][13] addressing both risk communication and clarification of patients' values. 12,14,15 Although clinicians generally support SDM, they are also often hesitant to practice it and often revert to a more authoritarian conversational model. 10,[16][17][18] In the Netherlands, the recent emphasis on value-based health care (VBHC) in health policy is thought to provide new opportunities for SDM, especially by using information based on patient-reported outcome measures (PROMs) in routine medical encounters.…”
Section: Introductionmentioning
confidence: 99%
“…These factors may well be key to the implementation of effective proactive care for older persons. Research has shown that patient involvement is difficult to implement in general practice [15,16], that patient preferences vary widely [4,17,18] and that older patients generally tend to be less involved compared to younger patients [4,5]. In addition to the availability and willingness of general practice professionals to invest time in patient involvement and shared decision making, the capacity and willingness of patients also demands attention [19].…”
Section: Comparison With Literaturementioning
confidence: 99%